PROMIS Global-10 poorly correlates with legacy outcomes for patients undergoing hip arthroscopy. Issue 1 (11th May 2021) - Bido, Jennifer; Sullivan, Spencer W; Dooley, Matthew S; Nawabi, Danyal H; Ranawat, Anil S; Kelly, Bryan T; Nwachukwu, Benedict U
ABSTRACT: The Patient-Reported Outcomes Measurement Information System (PROMIS) Global-10 assesses generic-related quality of life, but has not been well studied in the orthopaedic literature. The purpose was to compare PROMIS Global-10 and legacy hip-specific patient-reported outcome measures (PROMs) in patients undergoing hip arthroscopy for femoroacetabular impingement syndrome (FAIS). This study included patients who underwent primary hip arthroscopy with complete preoperative and 6-month post-operative follow-up. PROMIS Global-10 Physical (PROMIS-P) and Mental (PROMIS-M) components, as well as the modified Harris hip score (mHHS) and International Hip Outcome Tool-33 (iHOT-33) were assessed. PROM analysis included: post-operative changes, correlations, floor and ceiling effects and responsiveness. Final analysis included 112 patients. Average age and body mass index were 36.1±11.7 years and 24.8±3.9 kg/m 2, respectively. All 6-month PROMs, except PROMIS-M, were significantly improved compared to preoperative level ( P <0.02). Preoperatively, PROMIS-P was poorly correlated with mHHS and iHOT-33 ( r s  <0.4) whereas PROMIS-M was only poorly correlated with iHOT-33 ( r s  <0.4, 95% CI of 0.02–0.37). Post-operatively, the iHOT-33 was poorly correlated with both PROMIS measures ( r s  <0.4). The mHHS was fairly correlated with both PROMIS measures ( r s  <0.6) post-operatively. The effect sizes for mHHS and iHOT-33 were high ( d =1.2 and 1.40, respectively), whereas the effect sizes for PROMIS Global-10 were small ( d <0.3). PROMIS Global-10 demonstrated lower effect sizes and poor to fair correlation with legacy hip-specific PROMs, and appears to have a limited role in the assessment of patients undergoing hip arthroscopy for FAIS. Therefore, the PROMIS Global-10 may have a limited role in assessing patients with FAIS.